A tale of two life stages: The imprinting effect of macroeconomic contractions on later life entrepreneurship - Sotirakopoulos, Panagiotis; Mount, Matthew P.; Guven, Cahit; Ulker, Aydogan; Graham, Carol (Journal of Business Venturing, 2023)
Studies argue that macroeconomic contractions create immediate incentives for individuals to pursue entrepreneurship. However, research has not addressed whether past macroeconomic contractions imprint on individuals and influence their future entrepreneurship. Integrating literature on the business cycle and imprinting with insights from lifespan psychology, we develop and test competing theoretical arguments aligned to two distinct life stages about when a macroeconomic contraction will imprint on individuals to influence their future entrepreneurship, and how such effects are imprinted. Our findings show that only contractions experienced during early adulthood influence entrepreneurship and this effect is transmitted culturally via country-level preferences for time discounting.